Evaluación del malteado y fermentación en el proceso de cerveza artesanal tipo ale, utilizando el sorgo (Sorghum vulgare) como materia prima - Segovia Muñoz, SHeyling Alexis (2019)
This research project focuses on the production of a craft beer at the State Technical University of Quevedo, using barley and sorghum as malted cereals; due to its high starch content and nutritional properties, adding passion fruit pulp; with the aim of innovating and entering the market through the elaboration of this alcoholic beverage. In addition to assessing its alcohol content, pH, acidity and turbidity that guarantee product quality. A completely randomized experimental block design with factorial arrangement A * B was used. The factors studied were: Factor A (percentage of sorghum - percentage of barley) and Factor B (percentage of passion fruit pulp), corresponding to 9 treatments with 2 replicates, generating 18 experimental units. The study was conducted using ADEVA and TUCKEY tests, using the STATGRAPHICS statistical software; and for the treatment of significant differences in levels, the Tukey test was applied. This is how various incidents can be evidenced during the process of obtaining sorghum beer, such as the influence on soaking time, the humidity range and the temperature conducive to germination and after adding pale ale malt and fruit; consulting the sensory appreciation of the product. Key words: alcoholic beverage, hop, yeast, maduration